THE VOCABULARY OF THE CHRISTIAN CREED IN “NEW WORD INTERPRETER” (1803-1806) BY N. M. YANOVSKY (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-67-82The study is in line with the problems of the history of Russian lexicography and lexicology of the 18th - early 19th centuries. The novelty of the work is that that it first analyzes the features of the lexicographic description of the vocabulary of the Christian doctrine, contained in one of the fundamental publications of the Imperial Academy of Sciences - “New Word Interpreter” by N. M. Yanovsky, which is the largest collection of foreign words used in Russian by the end of the 18th century. As a result of the study, it was established that, despite the largely compilation nature and dependence of the “New Word Interpreter” on the “Church Dictionary” by P.A. Alekseev and the “Dictionary of the Russian Academy”, the work of N.M. Yanovsky is a valuable source for studying the borrowed vocabulary of Christian dogma of the 18th - early 19th centuries, reflecting its most productive thematic groups and incorporating a range of common religious words, which entered the Russian language in the 18th century and did not become the subject of interpretation in previous lexicographic works.Key words: Russian lexicography, vocabulary of Christian doctrine, religious vocabulary, N. M. Yanovsky, “New Word Interpreter”, 18th century, beginning of 19th century